2021
DOI: 10.1002/cre2.430
|View full text |Cite
|
Sign up to set email alerts
|

Study of the ultrastructure of Enterococcus faecalis and Streptococcus mutans incubated with salivary antimicrobial peptides

Abstract: Objectives Enterococcus faecalis has been associated with root canal infections, while Streptococcus mutans has a central role in the etiology of dental caries. One of the main reasons of endodontic failure has been associated to the presence of E. faecalis and the formation of biofilms. S. mutans inhabits the oral cavity, specifically the dental plaque, which is a multispecies biofilm formed on the hard surfaces of the tooth. The biofilm formation is the main factor determining the pathogenicity of numerous b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 88 publications
(100 reference statements)
2
6
0
Order By: Relevance
“…Intact, plump cell wall, and this was consistent with an earlier report (Blancas et al, 2021) Abbreviations: CS, Chitosan; PLL, polylysine; E. coli, Escherichia coli; E. faecalis, Enterococcus faecalis; P. aeruginosa, Pseudomonas aeruginosa; S. aureus, Staphylococcus aureus; TEM, transmission electron microscopy.…”
Section: E Faecalissupporting
confidence: 91%
“…Intact, plump cell wall, and this was consistent with an earlier report (Blancas et al, 2021) Abbreviations: CS, Chitosan; PLL, polylysine; E. coli, Escherichia coli; E. faecalis, Enterococcus faecalis; P. aeruginosa, Pseudomonas aeruginosa; S. aureus, Staphylococcus aureus; TEM, transmission electron microscopy.…”
Section: E Faecalissupporting
confidence: 91%
“…The remarkable antimicrobial activitiy of the AgNPs-based extracts suggests its usage as efficective disinfectants in health care yards. Furthermore, similar to others (Yi et al, 2011;Osonga et al, 2019), we demonstrated remakable antimicrobial activity against some oral pathogens such as S. mutants and to a lesser extent against E. faecalis which play a central role in dental carries and root canal infections (Krzyściak et al, 2014;Blancas et al, 2021;Tu et al, 2022). This implays the potential benefits of the AgNPs-based extracts in preventing dental diseases and promoting oral health.…”
Section: Antimicrobial Activitysupporting
confidence: 90%
“…This study evaluated three bacteria associated with root caries. S. mutans and S. sanguinis are frequently found in root caries, whereas E. faecalis is more commonly associated with endodontic infections [ 30 ]. However, a growing number of studies have observed it in carious lesions, periodontitis, and peri-implantitis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%